HYGIENIC ASSESSMENT OF THE CHILDREN'S PRESCHOOL ORGANIZATION "MAGIC CASTLE" - Turabaeva Z.K; Ochilova S.S (Scholar Express Journals, 2025)
The article discusses the results of the assessment of the sanitary-hygienic conditions of placement, equipment and maintenance of the territory and premises of a preschool organization. The socio-hygienic factors of the preschool educational institution, as well as the conditions for the upbringing and education of children in it, have a pronounced effect on the health of the younger generation.
Keywords: preschool-educational organization; sanitary conditions